(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
This paper presents psychological contract as a mental model of the employment relationship. In the first part comparison among psychological contract and formal employment contracts is made. Then, its basic components: employee’ beliefs regarding his obligations to the employer and employee’ beliefs regarding employer’ obligations to him are described. Generally, these components can be categorized as relational and transactional. Accordingly, there are two types of psychological contract: relational and transactional. In the next part, the psychological contract formation process (in which seeking and sense making of the information’s about work obligations are fundamental) is explained. In the final part importance and practical implications of psychological contract are discussed.